Activities of Daily Living - Andrzej Klimczuk (Encyclopedia of Family Studies, 2016)
Measurement of ability or inability to perform activities of daily living (ADLs) is important to in describing the functional status of a person and then implementing an intervention. Evaluations of ADLs are mainly used in nursing and in rehabilitation of people with disabilities and the elderly. Measuring ability to perform ADLs is crucial for the management of healthcare in aging societies. It is important to understand differences between categories of ADLs and challenges in their evaluation that are connected to the roles of family members.
Keywords: I10; 300; aging; health; disability; disease; health care; sociology of health; aging; and medicine